Pendampingan Pengelolaan Keuangan dan Pemasaran Digital bagi UMKM Desa Kemang - Sari, Lilis Permata; Argeto, Valentino; Widiastuti, Risma; Annisya, Dhea; Anggraini, Leriza Desitama; Gumano, Hendry Natanael; Purnamasari, Endah Dewi (Universitas Nusantara PGRI Kediri, 2024)
In the era of globalization that continues to develop, people are expected to adapt to increasingly advanced technological advances. This activity aims to strengthen MSME skills in financial management and digital marketing. This program helps people utilize social media and product branding techniques to increase sales and expand the market. The main target of this training and mentoring is the Kemang Village community, both from housewives, especially community leaders, to be more creative and innovative in managing their businesses, both in terms of financial records and marketing that can reach consumers widely. The implementation method used is through socialization and mentoring for the Kemang Village community. As a result, MSME actors in Kemang Village showed increased awareness and application of appropriate practices in marketing and financial management. This program shows how appropriate mentoring can encourage MSME growth and local economic welfare.